Gender differences in human single neuron responses to male emotional faces - Newhoff, Morgan; Treiman, David M.; Smith, Kris A.; Steinmetz, Peter N. (Frontiers in Human Neuroscience, 2015)
Well-documented differences in the psychology and behavior of men and women have spurred extensive exploration of gender's role within the brain, particularly regarding emotional processing. While neuroanatomical studies clearly show differences between the sexes, the functional effects of these differences are less understood. Neuroimaging studies have shown inconsistent locations and magnitudes of gender differences in brain hemodynamic responses to emotion. To better understand the neurophysiology of these gender differences, we analyzed recordings of single neuron activity in the human brain as subjects of both genders viewed emotional expressions. This study included recordings of single-neuron activity of 14 (6 male) epileptic patients in four brain areas: amygdala (236 neurons), hippocampus (n=270), anterior cingulate cortex (n=256), and ventromedial prefrontal cortex (n=174). Neural activity was recorded while participants viewed a series of avatar male faces portraying positive, negative or neutral expressions. Significant gender differences were found in the left amygdala, where 23% (n=15/66) of neurons in men were significantly affected by facial emotion, versus 8% (n=6/76) of neurons in women. A Fisher's exact test comparing the two ratios found a highly significant difference between the two (p<0.01). These results show specific differences between genders at the single-neuron level in the human amygdala. These differences may reflect gender-based distinctions in evolved capacities for emotional processing and also demonstrate the importance of including subject gender as an independent factor in future studies of emotional processing by single neurons in the human amygdala.